Impact of GST on small business sector in Haryana - Monika; Dr. Ritu (Innovative Research Thoughts, 2017)
Haryana's small businesses have been greatly affected by India's GST. This abstract explores GST's effects on small enterprises' potential and problems. Small Haryana firms have benefited from GST. It consolidated indirect taxes under a single tax structure. This streamlining has made tax compliance simpler for small firms. Small enterprises have become more competitive by eliminating cascading effects using the input tax credit system. Small enterprises may now reach clients beyond their state and compete, which has improved product quality and efficiency. Haryana's small enterprises also face GST issues.